Loosely coupled analysis strategy for melt-ablation modeling of thermal protection material in supersonic gas-particle two-phase impingement flow - Chong-You Lai; Tzong-Shyng Leu (Case Studies in Thermal Engineering, 2023)
In this study, a two-way fluid-thermal-ablation loosely coupled analysis strategy is used to investigate the melt-ablation process of the copper specimen plate in the scaled ducted launcher. By coupling a discrete-phase model for simulate the supersonic gas-particle two-phase exhaust plume impingement flow field of a small scaled solid propellant rocket and a solidification/melting model for simulate the melt-ablation process of a copper specimen plate, the ablation depth profile of the copper specimen plate at a burn time of 3.6 s is successfully estimated. The numerical model is validated by experimental-scale test which shows that the simulation results using the two-way fluid-thermal-ablation loosely coupled analysis strategy can accurately predict the ablation depth profile of the copper specimen plate.